Evaluating the leukogram in the dog and cat - PETAMIDIS (ΠΕΤΑΝΙΔΗΣ Θ.Α.) T. A.; MYLONAKIS (Μ. Ε. ΜΥΛΩΝΑΚΗΣ) M. E.; KOUTINAS (Α. Φ. ΚΟΥΤΙΝΑΣ) A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
Leukogram, an important part of complete blood count, includes the total count, absolute differential counts and leukocyte morphology. For a valid interpretation of the leukogram, proper blood sampling and post-sampling handling is considered a prerequisite. Total leukocyte counts in the clinically healthy adult dog and cat usually range from 6000 to 17000 /μΐ and from 5500 to 19500 /μΐ, respectively. Neutrophils, lymphocytes, monocytes, eosinophils and rarely basophils are the leukocytes recognized in the peripheral blood of these animal species. Leukocytosis and leukopenia may reflect pathological or physiologic responses to various endogenous or exogenous factors. Morphologic leukocyte changes may indicate an underlying inflammatory process (i.e. toxic changes), congenital and/or hereditary hematological abnormalities (i.e. Pelger-Hüet anomaly, Chediak-Higashi syndrome) and immune-mediated (i.e. systemic lupus erythematus) or neoplastic (i.e. lymphoid/myeloid leukemias) diseases. Detection of canine distemper virus inclusion bodies, Ehrlichia sp. morulae, Hepatozoon canis gamonts etc. in the cytoplasm of the various types of leukocytes is the most objective way to diagnose the relevant infectious diseases in the domestic carnivores.